Capturing Biochemical Diversity in Cassava (Manihot esculenta Crantz) through the Application of Metabolite Profiling - Drapal, Margit; Barros de Carvalho, Elisabete; Ovalle Rivera, Tatiana M.; Becerra López Lavelle, Luis Augusto (American Chemical Society, 2019)
Cassava (Manihot esculenta Crantz) is the predominant staple food in Sub-Saharan Africa (SSA) and an industrial crop in South East Asia. Despite focused breeding efforts for increased yield, resistance, and nutritional value, cassava breeding has not advanced at the same rapidity as other staple crops. In the present study, metabolomic techniques were implemented to characterize the chemotypes of selected cassava accessions and assess potential resources for the breeding program. The metabolite data analyzed was applied to describe the biochemical diversity available in the panel, identifying South American accessions as the most diverse. Genotypes with distinct phenotypic traits showed a representative metabolite profile and could be clearly identified, even if the phenotypic trait was a root characteristic, e.g., high amylose content.